2022
DOI: 10.1186/s12931-022-02194-4
|View full text |Cite|
|
Sign up to set email alerts
|

Race-specific reference values and lung function impairment, breathlessness and prognosis: Analysis of NHANES 2007–2012

Abstract: Background Spirometry reference values differ by race/ethnicity, which is controversial. We evaluated the effect of race-specific references on prevalence of lung function impairment and its relation to breathlessness and mortality in the US population. Methods Population-based analysis of the National Health and Nutrition Examination Survey (NHANES) 2007–2012. Race/ethnicity was analyzed as black, white, or other. Reference values for forced expir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“… 1 , 2 However, the clinical value of race adjustments has increasingly been questioned. 3 , 4 , 5 , 6 Although recent studies found no prognostic benefit of race-specific equations compared with “race-neutral” equations in mortality or respiratory events, 7 , 8 , 9 , 10 , 11 others continue to defend the use of race in prediction equations. 12 , 13 Race-specific equations are recommended by the most recent US and European guidelines 14 and are still used in clinical care and pulmonary research worldwide.…”
mentioning
confidence: 99%
“… 1 , 2 However, the clinical value of race adjustments has increasingly been questioned. 3 , 4 , 5 , 6 Although recent studies found no prognostic benefit of race-specific equations compared with “race-neutral” equations in mortality or respiratory events, 7 , 8 , 9 , 10 , 11 others continue to defend the use of race in prediction equations. 12 , 13 Race-specific equations are recommended by the most recent US and European guidelines 14 and are still used in clinical care and pulmonary research worldwide.…”
mentioning
confidence: 99%
“…In recent years, a substantive body of research has demonstrated the bias associated with use of race-specific predictive equations [ 26 , 29 , 34 , 36 ]. As such, we avoided the use of race-specific equations in all our analyses and opted to use Hankinson’s non-Hispanic White predictive equation for all races and the GLI race-neutral predictive equation in a secondary analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Given recent debates over the merits of race-specific predicative equations for spirometry, [ 28 , 29 , 34 36 ] in addition to Hankinson’s non-Hispanic White predictive equation of lung function, we also applied a race-neutral reference equation to explore differences in COPD prevalence and mortality. We used the Global Lung Function Initiative’s (GLI) race-neutral predictive equation for this secondary analysis [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…This restricted our ability to use multi-ethnic reference values, which could have impacted the estimation of prevalence at some sites. However, the NHANES equations have been shown to give similar prevalence estimates for airflow obstruction regardless of race-correction [ 35 ], while recent evidence suggests that race-correction may misclassify individuals with underlying disease [ 36 ].…”
Section: Strengths and Limitationsmentioning
confidence: 99%